2023
DOI: 10.1021/acsabm.2c01057
|View full text |Cite
|
Sign up to set email alerts
|

Fibrin Adsorption on Cardiovascular Biomaterials and Medical Devices

Abstract: Medical devices that are inserted in blood vessels always risk eliciting thrombosis, and the surface properties of such devices are thus of major importance. The initiating step for surface-induced pathological coagulation has been associated with adsorption of fibrinogen protein on biomaterial surfaces and subsequent polymerization into an insoluble fibrin clot. This issue gives rise to an inherent challenge in biomaterial design as varied surface materials must fulfill specialized roles while also minimizing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…The coatings were washed with excess water to remove any unattached material and dried under nitrogen before storage or use. AFM imaging, reported in a recent work, revealed that the dry coatings are flat with a root-mean-square roughness of around 0.5 nm. Further, the coatings proved to be robust and stable during repeated ice adhesion measurements (see Supporting Information, Figure S14).…”
Section: Methodsmentioning
confidence: 80%
“…The coatings were washed with excess water to remove any unattached material and dried under nitrogen before storage or use. AFM imaging, reported in a recent work, revealed that the dry coatings are flat with a root-mean-square roughness of around 0.5 nm. Further, the coatings proved to be robust and stable during repeated ice adhesion measurements (see Supporting Information, Figure S14).…”
Section: Methodsmentioning
confidence: 80%
“…Native fibrin is deposited at the site of arterial injury and, in part, determines the neointimal response, according to studies in the porcine coronary model. This evidence served as the impetus for the initial investigation into how fibrin-coated stents affected the arterial wall [79]. Twenty animals received 34 of these stents using the same porcine coronary model, and there were no immediate complications.…”
Section: Fibrin-based Coatingsmentioning
confidence: 99%
“…The most widespread medicaltechnological products containing noble metals are diagnostic electrophysiology catheters, diagnostic guide wires, and self-expanding stents. Such products contain Pt/Ir alloy marker bands [6], Au-coating media [7], and Ta marker dots at each edge [8], respectively.…”
Section: Introductionmentioning
confidence: 99%